Consciência política e participação no Orçamento Participativo em Cachoeiro de Itapemirim (ES, 2009-2012) - Leandro Vianna Silva Souza; Marcia Prezotti Palassi; Alfredo Rodrigues Leite da Silva (Ciências Sociais Unisinos)
The objective of this article is to understand the dynamics of political consciousness and citizen participation in Participatory Budgeting (PB) in Cachoeiro de Itapemirim (Espírito Santo State, Brazil) during 2009-2012. The discussion is based on the analysis model of political consciousness to understand the participation in collective actions from Sandoval (2001). It is a qualitative approach whose data were collected through participant observation, document analysis and semi-structured interviews with twenty-eight counselors of PB, subjected to content analysis (Bardin, 2004). The results reveal feelings of collective identity, contradictions between justice and injustice, political efficacy, antagonistic and adversary interests, willingness to act collectively, societal beliefs and values and evaluation of the PB’s goals. We can conclude that different types of political consciousness motivate the participation in this PB case: PB as an effective political mechanism for discussion and sharing of resources; PB as an opportunity to express the collective identity and prioritize their own community; PB as an opportunity to discuss power relations on the public budget. They are presented in a dynamic in which one interacts with the other on a daily basis without a clear boundary between them.